2017
DOI: 10.3390/ijerph14121472
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effects of Students’ Personality Traits on Pro-Environmental Behavioral Intentions in Response to Climate Change

Abstract: This study developed a model that examined the relationship between undergraduate students’ beliefs, norms and pro-environment behavioral intentions in the context of global climate change (GCC). The model was further evaluated to determine whether latent variables, such as sustainability value, environmental concern, social norms, perceived risk, pro-environmental attitude, as defined by the theory of planned behavior and value-belief-norm theory, significantly influenced students’ intentions towards pro-envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 95 publications
(111 reference statements)
5
48
0
3
Order By: Relevance
“…These results indicate that the positive personality of students indicates the tendency of students to act positively towards the environment better. The results are relevant to the research proposed by Yu and Yu (2017) which states that personality has a positive influence on one's willingness to act on the environment. In different definitions, it can be said that in carrying out an action someone refers to his personality (Hines et al, 1987).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…These results indicate that the positive personality of students indicates the tendency of students to act positively towards the environment better. The results are relevant to the research proposed by Yu and Yu (2017) which states that personality has a positive influence on one's willingness to act on the environment. In different definitions, it can be said that in carrying out an action someone refers to his personality (Hines et al, 1987).…”
Section: Resultsmentioning
confidence: 66%
“…However, in reality, information describing how the pattern of relationships between personality and intention to act on attitudes and responsibilities in the environment has not been widely discussed, but both are discussed more partially (Boyes & Stanisstreet, 2012;Kvasova, 2015;Yu & Yu, 2017). This study aims to determine the extent to which personality has an impact on students' intention to act in developing an environmentally responsible attitude.…”
Section: Introductionmentioning
confidence: 99%
“…While a plethora of new studies have recently considered challenging consumers' topics [4,25,26] in the study of consumers' satisfaction, two great research traditions emerged consistently: the cognitive and the affective. We organized the presentation of our findings in two steps.…”
Section: Resultsmentioning
confidence: 99%
“…A plethora of studies highlighted that consumers are immersed in their social context, and their thinking and emotion could be partly due to social influences [3] but can also be affected by their knowledge, previous attitudes, personality traits [4], and other variables. Hence, consumers' satisfaction and other affects associated to consumers' experiences should be deeper analyzed in order to explore them as predictors of consumption behavior [5].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that environmental value had positive influences on ecological intentions and pro-environmental behaviors [ 21 , 24 , 25 ]. For example, an investigation based on 275 undergraduate students indicated that the students’ intentions of adopting pro-environmental behavior were significantly affected by the sustainability value in the context of global climate change [ 26 ]. Therefore, residents with high ecological values are highly likely to perform environmental behaviors and accept a PCT scheme.…”
Section: Methodsmentioning
confidence: 99%